2020
DOI: 10.3390/app10072563
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Allicin against Plant Pathogenic Fungi and Unveiling the Underlying Mode of Action Employing Yeast Based Chemogenetic Profiling Approach

Abstract: Allicin (diallylthiosulfinate) is the principal organosulfur compound present in freshly damaged garlic tissue which exhibits a wide range of biological actions including antibacterial, antifungal, antiviral and anticancer properties. The antifungal activities of allicin were investigated against plant pathogenic fungi of agriculture importance. Furthermore, a yeast genome haploinsufficiency screening was also employed to decipher the antifungal mode of action of allicin. Wildtype and 1152 yeast mutant strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 66 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…In this context, the broad antimicrobial activity of organosulfur compounds derived from Allium spp. against a variety of bacteria and fungi has already been demonstrated in various in vitro studies [ 10 , 14 , 31 , 42 , 47 ]. Although the mechanism of action of organosulfur compounds is not yet deeply studied, the antimicrobial activity of these compounds could be associated with their capacity to react with the thiol groups of microbial enzymes, RNA synthesis blocking mechanisms, induction of oxidative stress and cellular apoptosis [ 15 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, the broad antimicrobial activity of organosulfur compounds derived from Allium spp. against a variety of bacteria and fungi has already been demonstrated in various in vitro studies [ 10 , 14 , 31 , 42 , 47 ]. Although the mechanism of action of organosulfur compounds is not yet deeply studied, the antimicrobial activity of these compounds could be associated with their capacity to react with the thiol groups of microbial enzymes, RNA synthesis blocking mechanisms, induction of oxidative stress and cellular apoptosis [ 15 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, scientific reports on the activity of organosulfur compounds from onion against plant pathogens are limited. On the contrary, more evidence on the antifungal activity of similar compounds from garlic, such as diallyl thiosulfinate or allicin [ 10 , 42 ] has been found. Some authors have reported the antifungal activity of an allicin against V. dahliae , both in vitro and in a leaf disk bioassay [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations